Pengaruh Literasi Media terhadap Ketelitian Mahasiswa Jurnalistik Universitas Bengkulu dalam Menilai Kebenaran Berita di Media Sosial - Velysa Anugrayni; Delfan Eko Putra (Lembaga Yasin AlSys, 2026)
The development of social media has accelerated the flow of information, including the dissemination of news whose truth has not been verified. This condition requires journalism students to have adequate media literacy and accuracy in assessing the truth of news. This study aims to analyze the influence of media literacy on the accuracy of Journalism students at Bengkulu University in assessing the truth of news on social media. This study employed a quantitative approach with an explanatory survey design. The research respondents consisted of 30 students selected through purposive sampling. Data were collected using a closed-ended Likert-scale questionnaire and analyzed using descriptive statistics and simple linear regression. The results showed that media literacy had a significant influence on students’ accuracy in assessing the truth of news, with a significance value of 0.000 (< 0.05), a regression coefficient of 1.064, and an R Square value of 0.719. These findings indicate that media literacy was able to explain 71.9% of the variation in students’ accuracy in assessing the truth of news on social media. The conclusion of this study affirms the importance of strengthening media literacy, information verification skills, and critical attitudes among journalism students in responding to the flow of news on social media. The implications of this study include theoretical contributions to the development of media literacy studies in journalism education and practical implications for universities in strengthening students’ competence in evaluating the truth of digital information.